The Sleep in the Critically Ill Aged Patients - Pedrão, Rodolfo Augusto Alves; Riella, Rodrigo Jardim; Valderramas, Silvia (Archives of Clinical and Biomedical Research, 2022)
Objective: To assess the characteristics and quality of sleep in critically ill older and younger adults and verify the differences between these groups. Check for associations between sleep and the perception of pain, noise, temperature, environmental luminance and the use of opiods and benzodiazepines. Method: Cross-sectional observational study, which evaluated lucid critically ill individuals, older and younger adults, with diseases of low or moderate severity. Sleep characteristics were measured using the Bispectral Index; sleep quality was measured using the Richards-Campbell Sleep Questionnaire; pain level was measured by Visual-Analog Scale; we recorded the ambient sound pressure, luminance and temperature, as well as the administered doses of opiods and benzodiazepines. Results: The medians of total sleep time, deep sleep time, pain intensity, luminance, ambient temperature, continuous sound pressure equivalent and perceived sleep quality were 237 minutes, 0 minutes, 1/10 point, 13.26 Lux, 22.4ºC, 57.27 decibels and 61/100 points, respectively. No older participant achieved deep sleep. In older people, pain and sleep quality are inversely correlated (ρ = -0.48; p<.05); in younger adults, volume and time of deep sleep were inversely correlated with environmental noise (ρ = -0.45; p<0.05 and ρ = -0.44; p<0.05, respectively). Conclusion: The sleep of adult patients with low and medium severity illnesses admitted to the ICU is of short duration and superficial, especially in the older patients. In these, pain perception is inversely correlated with sleep quality, while, in younger adults, environmental noise is inversely correlated with deep sleep.